1990
DOI: 10.1152/jn.1990.63.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of retinogeniculate transmission in cat on NMDA receptors

Abstract: 1. We have examined the possibility that N-methyl-D-aspartate (NMDA) receptors may be involved in the visual response of relay cells in the cat dorsal lateral geniculate nucleus (dLGN). The selective NMDA receptor antagonists D-2-amino-5-phosphonovalerate (APV) and 3-[(+/-)-2-carboxypiperazin-4-yl]-propyl-1-phosphonic acid (CPP) have been iontophoretically applied to X and Y cells in the dLGN and their effects on the visual response to a light spot flashed within the receptive field center determined. 2. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(55 citation statements)
references
References 0 publications
4
49
2
Order By: Relevance
“…An alternative explanation is that NMDARs could play a critical role in action potential generation and that the stimulation pattern is important in determining how much or how little a role. Supporting this idea is the observation that NMDAR antagonists can inhibit cell firing in the visual system (Miller et al, 1989;Sillito et al, 1990;Blitz and Regehr, 2003) (but see Bear et al, 1990) and in the hippocampus, as assessed by population spike size (Abraham and Mason, 1988;Burgard et al, 1989;Dahl et al, 1990). Here, we show that NMDARs do play a critical role in action potential generation in the hippocampal slice and that this role is dependent on stimulation pattern.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…An alternative explanation is that NMDARs could play a critical role in action potential generation and that the stimulation pattern is important in determining how much or how little a role. Supporting this idea is the observation that NMDAR antagonists can inhibit cell firing in the visual system (Miller et al, 1989;Sillito et al, 1990;Blitz and Regehr, 2003) (but see Bear et al, 1990) and in the hippocampus, as assessed by population spike size (Abraham and Mason, 1988;Burgard et al, 1989;Dahl et al, 1990). Here, we show that NMDARs do play a critical role in action potential generation in the hippocampal slice and that this role is dependent on stimulation pattern.…”
Section: Introductionsupporting
confidence: 53%
“…Previous work has shown that NMDARs can be important in cell firing, both in the visual system (Miller et al, 1989;Sillito et al, 1990;Blitz and Regehr, 2003) and in the dentate gyrus of the hippocampus (Abraham and Mason, 1988;Burgard et al, 1989;Dahl et al, 1990). The consequences of NMDAR inhibition on action potential generation in hippocampal neurons using LTPinducing stimulation, however, have not been studied previously.…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic NMDA receptors contribute significantly to retinogeniculate synaptic transmission (Sillito et al, 1990;Kwon et al, 1991;Esguerra et al, 1992;Ramoa and McCormick, 1994). NMDA receptor antagonists infused into the ferret LGN disrupt the pattern of sublamination of presynaptic retinogeniculate axons; retinal ganglion cell axon arbors are either abnormally large or are restricted in size but terminate in inappropriate locations within the LGN (Hahm et al, 1991).…”
Section: Abstract: Diffusible Messenger; Visual System; Lateral Genimentioning
confidence: 99%
“…MK-801 produces a doserelated spectrum of such motor dysfunctions as hyperactivity, stereotypies, or ataxia (Koek et al 1988;Murata and Kawasaki 1993). In addition, NMDA receptor antagonists including MK-801 also affect certain aspects of sensory processing (al-Amin and Schwarzkopf 1996;Cain et al 1997;Sillito et al 1990;Tang and Ho 1988). Therefore, it is essential to determine whether learning and memory deficits caused by MK-801 can be dissociated from nonspecific behavioral effects.…”
mentioning
confidence: 99%